The Sustainability of Complex Economic Systems. An Application of National Material Flow Analysis (MFA) to the Brazilian Economy - José Alberto da Costa Machado; Norbert Fenzl; Armin Mathis (tripleC: Communication, Capitalism & Critique)
A systemic approach to sustainability is suggested where the society-environment relationship is conceived in terms of complex, open systems. The sustainability of the relationship between society and the environment can be analyzed with the help of Material Flow Analysis (MFA). MFA reveals aspects of the economy that concern its relationship to the environment and can't be covered by monetary analyses. In this work material flows and their resulting indicators for the Brazilian economy from 1975 to 1995 are presented. The results show that the Brazilian economy in 1995 became much more intensive in material than in 1975. This development is in line with a global trend of material consumption becoming more intensive and unsustainable. The global economic system has not diminished its size, but expanded its consumption drive in relation to the environment.